School success, attitude towards science and interpersonal relations (2018)
Students who are excellent in their academic performance face challenges and difficulties associated with the social relationships they develop when living within the school environment. In similar studies, there are limitations such as the identification of the variables involved without reaching the level of correlation in the educational experience. The main objective of this research is to evaluate the impact of high academic performance on the interpersonal relationships of young adolescents in the I.E. College of the Sacred Heart of Jesus. The methodology used responds to the mixed approach, in the quantitative field follows a correlational method, from the qualitative field follows an ethnographic method, is designed for three phases and applies the instruments of the Davis empathy test (IRI), interview and nonparticipant observation. The results obtained show that there is a significant relationship between the academic success of the students and the quality of the relationships they have with their classmates, in general they tend to be less emotional and interested in cultivating significant bonds. Nowadays it is essential to consider in a holistic way the educational experience of the new generations, especially before the possibility of forming integral and well-being human beings that can be assertive in front of the obstacles of the future